Implements and Practices of Fishing in Kathekhola, Baglung, Nepal - Khatri, Dambar Singh; Kandel, Manish; Gautam, Prem Raj (Pragnya Sarathi प्रज्ञा-सारथि, 2023)
Fishing is the practise of catching fishes from different water resources. The main objective of this work was to list out the different tools and technique that are practiced in capture fishing in Kathekhola, Baglung, Nepal. The study was conducted during October 2021 to April.2022. The study assessed the fishing methods adopted by the fisherman in the study area by the purposive sampling and direct observations method adopted. Information was collected from 53 fishermen in the study area by the purposive sampling and direct observations method adopted in the area Kathekhola by regular field visit. The study identified that fisherman used hooks, cast net, gill net, fishing by hands, blocking and diverting water, umbrella fishing, Kure Thunne, use of plant extract as a traditional or conventional methods for fish catching. In addition, fisherman used insecticides and current for fishing. Electrofishing and insecticides are illegal fishing which were uncommon the study area. The livelihood of 20% fisherman depends on fishing. This study explored the various tools and techniques used to catch fish from the water bodies at Kathekhola, Baglung, Nepal. It is concluded from the study that the concerned body, administration, stakeholders would take necessary actions, strategy for use of convention fishing tools in Kathekhola.